2017
DOI: 10.3389/fphys.2017.00155
|View full text |Cite
|
Sign up to set email alerts
|

Adult Lysophosphatidic Acid Receptor 1-Deficient Rats with Hyperoxia-Induced Neonatal Chronic Lung Disease Are Protected against Lipopolysaccharide-Induced Acute Lung Injury

Abstract: Aim: Survivors of neonatal chronic lung disease or bronchopulmonary dysplasia (BPD) suffer from compromised lung function and are at high risk for developing lung injury by multiple insults later in life. Because neonatal lysophosphatidic acid receptor-1 (LPAR1)-deficient rats are protected against hyperoxia-induced lung injury, we hypothesize that LPAR1-deficiency may protect adult survivors of BPD from a second hit response against lipopolysaccharides (LPS)-induced lung injury. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Delving further into lipid mediated signaling other than S1P, we noted a significant increase in gene expression of LPA receptor 3 in the WT HO (1.78 fold increase with FDR of 0.014869) which is in agreement with hyperoxia studies carried out in rat BPD models [ 50 ]. Related studies in humans and rats revealed increased protein expression of autotaxin, Lpar1 and Lpar3 that co-localized to airway epithelial cells following exposure to hyperoxia [ 51 ].…”
Section: Discussionsupporting
confidence: 86%
“…Delving further into lipid mediated signaling other than S1P, we noted a significant increase in gene expression of LPA receptor 3 in the WT HO (1.78 fold increase with FDR of 0.014869) which is in agreement with hyperoxia studies carried out in rat BPD models [ 50 ]. Related studies in humans and rats revealed increased protein expression of autotaxin, Lpar1 and Lpar3 that co-localized to airway epithelial cells following exposure to hyperoxia [ 51 ].…”
Section: Discussionsupporting
confidence: 86%
“…In addition to changes in LPA and ATX, LPA receptor levels were increased in lung cells in both hyperoxia-and LPS-induced experimental acute lung injuries [79,81]. The studies using LPA receptor-deficient mice or antagonists provided solid data to support that LPA receptors, especially LPA 1 , act as proinflammatory GPCRs during the progression of hyperoxia-or LPSinduced acute lung injury and sepsis [79,88,89]. Interestingly, LPA 1 seems to have no effects on alveolar-capillary integrity as no changes of LPSinduced BAL protein were detected in LPA 1deficient mice or ki16425-treated mice [79].…”
Section: Pro-and Anti-inflammatory Roles Of Atx-lpa-lpa Receptor Axismentioning
confidence: 99%
“…27,28 Recent studies have found that LPAR1 is a carcinogenic factor and able to enhance metastasis and invasion in several cancers, such as melanoma, breast cancer and ovarian cancer. Here, we identified that the downstream effector of miR-892b is lysophosphatidic acid receptor 1 (LPAR1).…”
Section: Introductionmentioning
confidence: 99%